Предмет: Математика,
автор: Sun77024656
Упростить выражение
(Х-5)(4х+2)-(2х-5)(2х+2)
Ответы
Автор ответа:
0
= 4х^2 - 20x + 2х - 10 - (4x^2 -10x + 4x - 10) =
= 4x^2 - 20x + 2x - 10 - 4x^2 + 10x - 4x + 10 =
= - 18x -10 + 6x + 10 = - 12x
= 4x^2 - 20x + 2x - 10 - 4x^2 + 10x - 4x + 10 =
= - 18x -10 + 6x + 10 = - 12x
Похожие вопросы
Предмет: Геометрия,
автор: osospcrc
Предмет: Информатика,
автор: zhamkochyanzha
Предмет: Биология,
автор: fairyforest032805
Предмет: Биология,
автор: vol4ik1
Предмет: Алгебра,
автор: Ksholina